Estudo fitoquímico de Helicteres velutina K. Schum (Sterculiaceae) e avaliação do seu potencial larvicida contra Aedes aegypti L. (Diptera: Culicidae) - Fernandes, Diégina Araújo (2017)
Natural products have been used by humankind since immemorial times to relieve and cure severals diseases, and the ethnic-pharmacology knowledge of plant species has aroused interest in research aimed at the discovery of bioactive molecules. The emergence of new diseases transmitted by Aedes aegypti L., linked to resistance to larvicides and insecticides in the market, makes it necessary to search for alternatives to vector combat. In this context the Brazil stands out because it has a great potential of natural resources that lead to the development of native flora bioproducts.Within this diversity was sought through a pioneering study from view point chemical and biological of the ethanolic extract gross obtained from the aerial parts of the species Helicteres velutina K. Schum (Sterculiaceae), commonly know in Brazil as “pitó” is popularly used by the tribe indigenous Pankararé in Bahia, as insect repellent, isolate and identify their chemical constituents, as well evaluate their larvicidal potential.For the phytochemical study, the ethanolic extract gross was solubilized in EtOH:H2O (7:3) and partitioned with Hex.; CH2Cl2; AcOEt; n-BuOH, obtaining their respective phases, in addition to the hydroalcoholic phase. 8g of the dichloromethane phase was subjected to column chromatography using silica flash and/or Sephadex-LH 20 as stationary phases.This chromatographic process led to the apartness of five chemical constituents, whose chemical structures were defined by the interpretation of infrared, RMN 1H e 13C spectra and 2D, as well as comparisons with literature models. The isolated substances were three flavonoids: Hv-1 - 3,5,7,4'-tetrahydroxyflavone (Kaempferol); Hv-2 - Kaempferol-3-O-β-D-(6´´-E-p-coumaroyl) glucopyranoside (Tiliroside); Hv-3 - 7,4’-di-O-methyl-8-O-sulphateflavone (Isoscutellarein sulphate); one triterpene from the series oleanane - Hv-4 – Acid 3β-hydroxy-olean-12-en-28-oic (Oleanolic acid); and a steroid - Hv-5 - Sitosterol-3-O-D- glucopyranoside (β-sitosterol glycosylated). A preliminary study to evaluate the larvicidal activity of the ethanolic extract gross of the aerial parts of Helicteres velutina demonstrated excellent activity against larvae in the L4 stage of Aedes aegypti, with the 10.000 ppm dose dose of killing 100% of the larvae after 24 h of exposure and the CL50 was estimated to be 2.983 ppm according to Tukey's test, thus characterizing itself as a promising alternative to be used in an integrated control system of this vector, which demands the continuity of its studies.